Uptake and predictors of early postnatal follow-up care amongst mother-baby pairs in South Africa: Results from three population-based surveys, 2010-2013. - Larsen, Anna; Cheyip, Mireille; Aynalem, Getahun; Thu-ha Dinh; Jackson, Debra; Ngandu, Nobubelo; Chirinda, Witness; Mogashoa, Mary; Kindra, Gupreet; Lombard, Carl; Goga, Ameena; Dinh, Thu-Ha (Journal of Global Health, 2017)
Background: Achieving World Health Organization (WHO) recommendations for postnatal care (PNC) within the first few weeks of life is vital to eliminating early mother-to-child transmission of HIV (MTCT) and improving infant health. Almost half of the annual global deaths among children under five occur during the first six weeks of life. This study aims to identify uptake of three PNC visits within the first six weeks of life as recommended by WHO among South African mother-infant pairs, and factors associated with uptake.Methods: We analyzed data from three facility-based, nationally representative surveys (2010, 2011/12 and 2012/13) primarily designed to determine the effectiveness of the South African program to prevent MTCT. This analysis describes the proportion of infants achieving the WHO recommendation of at least 3 PNC visits. Interviews from 27 699 HIV-negative and HIV-positive mothers of infants aged 4-8 weeks receiving their six week immunization were included in analysis. Data were analyzed using STATA 13.0 and weighted for sample ascertainment and South African live births. We fitted a multivariable logistic regression model to estimate factors associated with early PNC uptake.Results: Over half (59.6%, 95% confidence interval (CI) = 59.0-60.3) of mother-infant pairs received the recommended three PNC visits during the first 6 weeks; uptake was 63.1% (95% CI = 61.9-64.3) amongst HIV exposed infants and 58.1% (95% CI = 57.3-58.9) amongst HIV unexposed infants. Uptake of early PNC improved significantly with each survey, but varied significantly by province. Multivariable analysis of the pooled data, controlling for survey year, demonstrated that number of antenatal visits (4+ vs <4 Adjusted odds ratio (aOR) = 1.13, 95% CI = 1.04-1.23), timing of initial antenatal visits (≤12 weeks vs >12 weeks, aOR = 1.13, 95% CI = 1.04-1.23), place of delivery (clinic vs hospital aOR = 1.5, 1.3-1.6), and infant HIV exposure (exposed vs unexposed aOR = 1.2, 95% CI = 1.1-1.2) were the key factors associated with receiving recommended PNC visits.Conclusions: Approximately 40% of neonates did not receive three or more postnatal care visits in the first 6 weeks of life from 2010-2013. To improve uptake of early PNC, early antenatal booking, more frequent antenatal care attendance, and attention to HIV negative women is needed.